Type 2 Diabetes Mellitus Non-genetic Rhesus Monkey Model Induced by High Fat and High Sucrose Diet - Lu, Shuai-yao.; Qi, Su-dong.; Zhao, Yuan.; Li, Yan-yan.; Yang, Feng-mei.; Yu, Wen-hai.; Jin, Ma; Chen, Li-xiong.; Wang, Jun-bin.; He, Zhan-long.; Li, Hong-jun. (Experimental and Clinical Endocrinology & Diabetes, 2015)
To build an ideal animal model for studying the mechanism of occurrence, developing and treating of diabetes become a more important issue, facing with the fact that the big threat of diabetes to human health has been worsen. First, we used the normal control diets or the high-fat/high-sucrose diets to feed the adult rhesus monkeys and the macaques induced by the high-fat/high-sucrose diets in the high-fat/high-sucrose group and the type 2 diabetes mellitus (T2DM) group developed the hyperglycemia, hyperinsulinemia at 6 months in accordance with the precious researches that reported that minipigs, rats and mice could develop hyperglycemia, hyperinsulinemia, hyperlipidemia and obesity after being induced with high-fat/high-carbohydrate diets. Second, the rhesus monkeys in T2DM group were injected STZ at a low dosage of 35 mg/kg BW to induce glucose persistent elevation which maintained pretty well after 12 months. Third, we took the assay of glucose tolerance test and insulin resistance index, assessed the changing tendency of serum resistin and analysed the pathological characteristics of the tissues like pancreas and liver by staining in different ways. The results indicate the rhesus monkeys in T2DM group have lots of clinical features of T2DM. The experimental non-genetic T2DM rhesus monkeys model not only contribute to simulating of clinical manifestations and pathological features of human T2DM, but also may be a good kind of model for research on the treatment of T2DM and for new drugs evaluation.
Keywords: type 2 diabetes mellitus; high-fat/high-sucrose diets; animal model; rhesus monkey